2022
DOI: 10.3389/fnagi.2022.885500
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Parkinson’s Disease: From Mechanistic Insights to Therapy

Abstract: Parkinson’s disease (PD) is one of the most common neurodegenerative movement disorders worldwide. There are currently no cures or preventative treatments for PD. Emerging evidence indicates that mitochondrial dysfunction is closely associated with pathogenesis of sporadic and familial PD. Because dopaminergic neurons have high energy demand, cells affected by PD exhibit mitochondrial dysfunction that promotes the disease-defining the loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 208 publications
0
39
0
Order By: Relevance
“…Finally, miR-128 could prevent the activation of caspases-8, -9 and -3, eventually shutting down both the intrinsic and extrinsic pathways of apoptosis. In addition to that, mitochondrial dysfunction is known to be associated with both the sporadic and familial forms of PD and various interventions targeting mitochondrial impairment and superoxide production have been reported in the past ( Luo et al, 2015 ; Gao et al, 2022 ). Interestingly, our study revealed that miR-128 over-expression could be an important strategy in controlling mitochondrial superoxide production during PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-128 could prevent the activation of caspases-8, -9 and -3, eventually shutting down both the intrinsic and extrinsic pathways of apoptosis. In addition to that, mitochondrial dysfunction is known to be associated with both the sporadic and familial forms of PD and various interventions targeting mitochondrial impairment and superoxide production have been reported in the past ( Luo et al, 2015 ; Gao et al, 2022 ). Interestingly, our study revealed that miR-128 over-expression could be an important strategy in controlling mitochondrial superoxide production during PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanisms underlying the sex differences in brain injury responses and development of neurodegenerative conditions remain to be elucidated, alterations in mitochondrial functions and immune responses are considered the key candidates. Mitochondria dysfunction is thought to be involved in the pathogenesis of many neurodegenerative diseases ( Lin and Beal, 2006 ; Wang et al, 2019 , 2020 ; Gao et al, 2022 ). Mitochondria play an important role in cell death via their release of pro-apoptotic factors after undergoing outer membrane permeabilization, which commonly occurs after TBI ( Cheng et al, 2012 ; Fischer et al, 2016 ).…”
Section: Sex Differences In Mtbi and Neurodegenerationmentioning
confidence: 99%
“…Previous preclinical TBI studies have implicated the involvement of neuronal excitotoxicity, increases in intracellular calcium, free radical production, mitochondrial dysfunction, and inflammatory mediators ( Globus et al, 1995 ; Werner and Engelhard, 2007 ; Hawryluk and Manley, 2015 ) within the injury response cascade, as well as the disruption of blood brain barrier integrity ( Shlosberg et al, 2010 ), activation of glia ( Myer et al, 2006 ), and inhibition of regeneration ( McGraw et al, 2001 ; di Giovanni et al, 2005 ; Itoh et al, 2007 ). Within these pathways, mitochondrial dysfunction and chronic inflammation have been suggested to be involved in long-term processes leading to neurodegenerative conditions ( Wang et al, 2019 , 2020 ; Gao et al, 2022 ). However, the study of many of these processes in preclinical models of mTBI has been limited to the acute phase of injury and it remains to be determined if any of these processes are responsible for the emergence of neurodegeneration years after injury exposure.…”
Section: Introductionmentioning
confidence: 99%
“…At present, PD affect almost 1-2% of the world population, whereas the estimated prevalence rate would be double in 2040 [4][5][6]. Based on previous studies, the complicated mechanisms for PD development were ascribed to mitochondrial dysfunction, oxidative stress, apoptosis and neuroinflammation [3,7,8]. To date, many efforts have been made to explore the potential mechanism to counteract PD, however, it is still lack efficient therapy.…”
Section: Introductionmentioning
confidence: 99%